Postcard from Jacobus van 't Hoff to Georg Bredig, March 1894 - Hoff, J. H. van 't (Jacobus Henricus) (1894)
Jacobus Henricus van’t Hoff (1852-1911) writes to Georg Bredig (1868-1944) about working in his (van't Hoff's) laboratory. Van't Hoff is considered to be one of the founding fathers of physical chemistry. In 1901 van’t Hoff received the first Nobel prize in Chemistry “in recognition of the extraordinary services he has rendered by the discovery of the laws of chemical dynamics and osmotic pressure in solutions.” Around 1894, Georg Bredig completed a portion of his post-doctoral work in van’t Hoff’s laboratory in Amsterdam.
Keywords: Hoff, J. H. van 't (Jacobus Henricus), 1852-1911; Bredig, Georg, 1868-1944